Phase‐diagram‐guided method for growth of a large crystal of glycoside hydrolase family 45 inverting cellulase suitable for neutron structural analysis. (25th September 2013) - Nakamura, Akihiko; Ishida, Takuya; Fushinobu, Shinya; Kusaka, Katsuhiro; Tanaka, Ichiro; Inaka, Koji; Higuchi, Yoshiki; Masaki, Mika; Ohta, Kazunori; Kaneko, Satoshi; Niimura, Nobuo; Igarashi, Kiyohiko; et al.
<x xml:space="preserve">Abstract</x> Neutron protein crystallography (NPC) is a powerful tool for determining the hydrogen position and water orientation in proteins, but a much larger protein crystal is needed for NPC than for X‐ray crystallography, and thus crystal preparation is a bottleneck. To obtain large protein crystals, it is necessary to know the properties of the target protein in the crystallization solution. Here, a crystal preparation method of fungal cellulase PcCel45A is reported, guided by the phase diagram. Nucleation and precipitation conditions were determined by sitting‐drop vapor diffusion. Saturation and unsaturation conditions were evaluated by monitoring crystal dissolution, and a crystallization phase diagram was obtained. To obtain a large crystal, crystallization solution was prepared on a sitting bridge (diameter = 5 mm). Initial crystallization conditions were 40 µl of crystallization solution (40 mg ml−1 protein with 30.5% 3‐methyl‐1, 5‐pentanediol in 50 mM tris‐HCl pH 8.0) with a 1000 µl reservoir (61% 3‐methyl‐1, 5, ‐pentanediol in 50 mM tris‐HCl pH 8.0) at 293 K. After the first crystal appeared, the concentration of precipitant in the reservoir solution was reduced to 60% to prevent formation of further crystals. Finally, we obtained a crystal of 6 mm3 volume (3 mm × 2 mm × 1 mm), which was suitable for neutron diffraction.